Anonymity-based intra–inter and multiple layer service dependent security-aware packet scheduling algorithm (AIIMLSDSPS). Issue 4 (18th May 2020) - Nandakumar, R.; Nirmala, K.
ABSTRACT: The concept of anonymity is included for enhancing the efficiency of security aware packet scheduling by introducing, Anonymity-based Intra and inter and multiple layer service dependent security aware packet scheduling algorithm (AIIMLSDSPS). The anonymity of the source locations are often violated by the intruders through traffic analysis and RF localization techniques. The proposed fake source-location method produces the fake sources into the network in order to confuse the intruder. When the original sources send event messages with secured routing policy, the fake sources are generated dynamically. Fake sources then construct several fake paths in the network. Thus, the proposed fake source-location method minimizes the chances of intrusion and reduces the packet loss with minimal latency and reduced overhead. However, as number of fake paths and fake messages increases, energy consumption of each source is also increases.